Korupsi Sebagai Patologi Sosial Sistemik Di Indonesia Dan Kegagalan Hukum Pidana Dalam Menciptakan Efek Jera - Amelia Saputri; Annisya Nurhasanah; Arsyanika Nhayla Ananda; Indri Kurnia Saputri; Wevy Efticha Sary (GLOBAL SCIENTS PUBLISHER, 2025)
Corruption in Indonesia can no longer be understood merely as individual legal violations but has evolved into a systemic social pathology that is continuously reproduced through mechanisms of social anomie, dysfunctional social control, and the weakness of criminal law institutions. This normative juridical research analyses why corruption-related criminal law, despite imposing severe penalties up to life imprisonment and the death penalty, persistently fails to break the chain of reproduction of corrupt behaviour. Employing Robert K. Merton’s anomie theory, Emile Durkheim’s theory of social pathology, and Sudarto–Barda Nawawi Arief’s concept of criminal law dysfunction, the study concludes that corruption has become an alternative norm among bureaucratic and political elites, limited reverse proof (Article 37 of the Anti-Corruption Law) and the rare imposition of minimum sentences eliminate deterrent effects, while impunity for corporate actors and politically exposed persons reinforces structural anomie. The research recommends the adoption of full reverse proof, elimination of prosecutorial discretion under Article 4 of the Anti-Corruption Law, and stricter corporate criminal liability provisions in the new Criminal Code that will be gradually implemented from 2026 onward.